Ruang Dialog Hukum dan Ekonomi Islam Kontemporer - Zahrul Akbar (Al-Widad, 2025)
Ideally, Islamic law and Islamic economics are expected to synergize in shaping a just social and economic order based on sharia principles. However, in contemporary reality, the two are often positioned separately, resulting in a gap between normative values and modern economic practices. This study aims to analyze the space for dialogue between Islamic law and Islamic economics in a contemporary context by examining the dynamics of the development of Islamic law, the transformation of Islamic economic thought, and the integration of the two in responding to modern challenges. This research employs a qualitative-descriptive approach through a library research method. The findings indicate that the integration of Islamic law and Islamic economics is an essential prerequisite for normative legitimacy and the effectiveness of sharia-based economic practices. This study contributes to enriching scholarly discourse through an integrative perspective between sharia values and contemporary economic practices.